2013
DOI: 10.1088/0953-4075/46/4/045201
|View full text |Cite
|
Sign up to set email alerts
|

Tunnelling of a molecule with many bound states in three dimensions

Abstract: We study in three dimensions a diatomic homo-nuclear molecule with many bound states incident upon a potential barrier. We consider different initial states for the molecule and take into account transitions between rotational states of the molecule during the process in which the entire molecule tunnels past or is reflected by the external potential barrier. We show the manner in which the transmission resonances are affected by having many bound states. We find that the transmission probability profile in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…for an exciton with the same physical parameters, e.g. mass, Bohr radius, binding energy) was also observed in another study concerning the tunneling of a molecule in three dimensions with many bound states [52]. That these features are observed in 1D tunneling may be a result of our using a hydrogenic binding function, more realistic than the binding potentials used in previous molecular tunneling studies.…”
Section: Effect Of Changing ãsupporting
confidence: 68%
See 1 more Smart Citation
“…for an exciton with the same physical parameters, e.g. mass, Bohr radius, binding energy) was also observed in another study concerning the tunneling of a molecule in three dimensions with many bound states [52]. That these features are observed in 1D tunneling may be a result of our using a hydrogenic binding function, more realistic than the binding potentials used in previous molecular tunneling studies.…”
Section: Effect Of Changing ãsupporting
confidence: 68%
“…The most obvious is an extension from a one-dimensional hydrogenic exciton model to a three-dimensional model, which could take into account factors such as exciton angular momentum. Calculations of reflection and transmission probabilities for a three-dimensional homonuclear molecule incident upon an external barrier were carried out in [41] and [52]. However, it should be noted that the results in [41] were qualitatively similar to results obtained from studies on 1D homonuclear molecule tunneling, and that novel qualitative results obtained in [52] (e.g.…”
Section: Future Work and Connection To Realistic Systemsmentioning
confidence: 57%
“…On the other hand, when K a = π/2 + iK a , the equation with + sign corresponds to the case where sgn(J) = sgn(D) = sgn(V 0 ), while that with − sign corresponds to the case where sgn(J) = sgn(V 0 ) = sgn(D). Substituting K a obtained by ( 37) into (10) gives…”
Section: Bound States In the Continuummentioning
confidence: 99%
“…It had been shown that the probability of tunnelling of an object possessing an internal degree of freedom -for example, a diatomic molecule -through a barrier may greatly exceed that of a structureless object with similar properties due to appearance of quasi-bound states in the combined scattering and molecular binding potentials [5][6][7]. Furthermore, interaction of a molecule with the ex- * fumika@physics.ubc.ca † litinskaya@gmail.com ‡ unruh@physics.ubc.ca ternal potential can induce transitions between molecular states due to coupling between relative and centre of mass (CM) coordinate degrees of freedom [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, Shegelski used this method to extend previously obtained results and thereby revealed more details and behaviours for tunnelling in one and three dimensions [9,10]. Razavy's method was used in studies of molecules having two bound states [9,10], many bound states [11,12], and two bound states with a continuum of unbound states [13]. Formation of a molecule in a bound state by having two atoms incident upon a potential was demonstrated using this method [14].…”
Section: Introductionmentioning
confidence: 95%